Case report: Rituximab combined with plasma exchange treatment for systemic lupus erythematosus complicated with thrombotic microangiopathy and non-cirrhotic portal hypertension - Huang, Jinmei; Fan, Wei; Chen, Xuyan; Wu, Shufan; Dong, Zhigao; Zhang, Yi; Lin, Yiwan; Xiao, Pingping (Frontiers in Immunology, 2025)
IntroductionSystemic lupus erythematosus (SLE) complicated by thrombotic microangiopathy (TMA) and non-cirrhotic portal hypertension (NCPH) is rare. We present a case of a female patient with SLE who developed TMA and NCPH and responded positively to rituximab and plasma exchange treatment.Case descriptionA 53-year-old woman was admitted with 6 h of confusion. Upon admission, she was diagnosed with SLE complicated by lupus encephalopathy, blood system impairment, cardiomyopathy, and nephritis. Initial treatment with high-dose methylprednisolone, immunoglobulin shock therapy, and tacrolimus (1 mg, twice daily) improved her symptoms and laboratory indicators. However, after a pulmonary infection and infection with the 2019 novel coronavirus, the patient’s condition deteriorated further. She experienced confusion and a delayed response. Hemoglobin levels and platelet counts decreased, lactate dehydrogenase and creatinine levels increased, and the percentage of peripheral schistocytes was approximately 6.5%. Abdominal ultrasonography revealed a substantial amount of ascites, diffuse liver lesions, splenomegaly, and splenic varices. Enhanced computed tomography revealed diffuse liver disease along the portal veins, intrahepatic lymphatic dilatation, esophageal and gastric varices, a splenorenal vein shunt, and splenomegaly. The patient was negative for hepatitis virus, autoimmune liver disease antibodies, ceruloplasmin, and tumor markers. Therefore, SLE complicated by TMA and NCPH was considered. She was treated with high-dose methylprednisolone (500 mg) for 3 days and immunoglobulin (0.4 g/kg/day) for 5 days, followed by rituximab (500 mg) for suppressive immunotherapy combined with plasma exchange (seven times), low-molecular-weight heparin (5,000 U every 12 h) for anticoagulation, and a diuretic. The patient’s symptoms and laboratory indicators improved.ConclusionThis case suggests that a combination of rituximab, plasma exchange, anticoagulation, and diuretics may be an effective treatment for patients with SLE complicated by TMA and NCPH.